1997
DOI: 10.1093/emboj/16.22.6684
|View full text |Cite
|
Sign up to set email alerts
|

Several cooperating binding sites mediate the interaction of a lysosomal enzyme with phosphotransferase

Abstract: Lysosomal targeting of soluble lysosomal hydrolases is mediated by mannose 6-phosphate receptors, which recognize and bind mannose 6-phosphate residues in the oligosaccharide chains of proteins destined for delivery to lysosomes. This recognition marker is generated by the sequential action of two enzymes, the first of which, UDP-N-acetylglucosamine phosphotransferase, recognizes lysosomal enzymes on the basis of a structural determinant in their polypeptide chains. This recognition event is a key step in lyso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
52
0
3

Year Published

1998
1998
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 35 publications
4
52
0
3
Order By: Relevance
“…The distance of ϳ34 Å between ␣-carbon atoms of critical lysine residues appears to be a general feature of the phosphorylation signal. This distance was demonstrated in our earlier study (17) for cathepsin D as well as cathepsin L (14) and is consistent with results obtained for two other proteins, DNase I (15, 29) and aspartylglucosaminidase (16). In the case of aspartylglucosaminidase, mutation of two lysine residues, Lys-183 in the ␣ subunit and Lys-214 in the ␤ subunit, was found to inhibit mannose phosphorylation by 96%.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The distance of ϳ34 Å between ␣-carbon atoms of critical lysine residues appears to be a general feature of the phosphorylation signal. This distance was demonstrated in our earlier study (17) for cathepsin D as well as cathepsin L (14) and is consistent with results obtained for two other proteins, DNase I (15, 29) and aspartylglucosaminidase (16). In the case of aspartylglucosaminidase, mutation of two lysine residues, Lys-183 in the ␣ subunit and Lys-214 in the ␤ subunit, was found to inhibit mannose phosphorylation by 96%.…”
Section: Discussionsupporting
confidence: 89%
“…On the basis of these results, a relatively simple model involving lysine residues was proposed as a general phosphorylation signal for lysosomal proteins. Similar involvement of lysine residues (15,16) has since been demonstrated for other proteins, and it is now widely accepted that lysine residues are the primary determinants for mannose phosphorylation of a wide range of proteins by the transferase.…”
supporting
confidence: 58%
See 2 more Smart Citations
“…A number of studies from our laboratory and others have shown that the protein recognition domain of acid hydrolases is a complex conformation-dependent determinant that includes a number of critical lysine residues (16)(17)(18)(19)(20)(21)(22)(23). On this basis, it seems likely that the interaction of an acid hydrolase with GlcNAc-1-phosphotransferase would involve multiple contacts between the surfaces of the two proteins.…”
mentioning
confidence: 99%